Direct evidence for spinal cord involvement in placebo analgesia. - Eippert, F; Finsterbusch, J; Bingel, U; Büchel, C (2009)
Placebo analgesia is a prime example of the impact that psychological factors have on pain perception. We used functional magnetic resonance imaging of the human spinal cord to test the hypothesis that placebo analgesia results in a reduction of nociceptive processing in the spinal cord. In line with behavioral data that show decreased pain responses under placebo, pain-related activity in the spinal cord is strongly reduced under placebo. These results provide direct evidence for spinal inhibition as one mechanism of placebo analgesia and highlight that psychological factors can act on the earliest stages of pain processing in the central nervous system.